2011
DOI: 10.1095/biolreprod.110.089532
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Interaction Between Unfolded-Protein-Response Key Protein HSPA5 and Estrogen Signaling in Human Endometrium1

Abstract: The human endometrium is a dynamic tissue that undergoes cyclic changes under the influence of steroid hormones as well as numerous local paracrine and autocrine factors. Heat shock 70 kDa protein (HSPA5; also known as GRP78/BiP), a molecular chaperone within the endoplasmic reticulum, plays crucial roles in normal cellular processes as well as in stress conditions, in which it is a central regulator for the unfolded protein response (UPR). We hypothesized that HSPA5 expression level is variable throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 39 publications
3
39
0
Order By: Relevance
“…Furthermore, we also demonstrated that histologically normal endometrium can variably express GRP78, a finding that is consistent with previously reports [36]. To determine whether or not estrogen plays a direct effect on ER stress in human EC cells, Guzel and colleagues directly applied estradiol to Ishikawa cells, and showed no GRP78 induction [37]. In fact, pre-treatment of both Ishikawa cells and primary endometrial stromal cells appeared to abrogate chemically-induced ER stress, further supporting that estrogen exposure may not directly increase endometrial ER stress [37].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we also demonstrated that histologically normal endometrium can variably express GRP78, a finding that is consistent with previously reports [36]. To determine whether or not estrogen plays a direct effect on ER stress in human EC cells, Guzel and colleagues directly applied estradiol to Ishikawa cells, and showed no GRP78 induction [37]. In fact, pre-treatment of both Ishikawa cells and primary endometrial stromal cells appeared to abrogate chemically-induced ER stress, further supporting that estrogen exposure may not directly increase endometrial ER stress [37].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, HSPA5 protein expression was up-regulated in the midsecretory endometrial tissues of both RM and RIF patients. This is particularly relevant because it has been recently described that HSPA5 expression fluctuates in the normal endometrium during the menstrual cycle, with the lowest degree of expression in the midsecretory phase (43). Thus, deregulated HSPA5 expression might play a role in defective implantation.…”
Section: Galgani T Cells and Er Stress In Infertility Fertil Sterilmentioning
confidence: 98%
“…This can occur in normal developmental and physiological contexts, like establishing the vasculature of a placenta (29) and promoting wound healing (30,31), as well as pathological conditions, like increasing tumor vascularization (10,32). Although a large number of studies exist to demonstrate activation of both pathways in these various tissues and conditions, nearly all of them study the pathways independently, and, thus, very little is known about possible interactions between these pathways on shared transcriptional targets like VEGF.…”
Section: Imentioning
confidence: 99%